2010
DOI: 10.1021/la100166f
|View full text |Cite
|
Sign up to set email alerts
|

Iodide Impurities in Hexadecyltrimethylammonium Bromide (CTAB) Products: Lot−Lot Variations and Influence on Gold Nanorod Synthesis

Abstract: Recent reports [Smith and Korgel Langmuir 2008, 24, 644-649 and Smith et al. Langmuir 2009, 25, 9518-9524] have implicated certain hexadecyltrimethylammonium bromide (CTAB) products with iodide impurities, in the failure of a seed-mediated, silver and surfactant-assisted growth protocol, to produce gold nanorods. We used two of the three "suspect" CTAB products and a "good" CTAB product in the protocol, varying silver nitrate solutions in the growth solutions. We obtained excellent gold nanorod samples as witn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 25 publications
4
80
0
Order By: Relevance
“…[28] Later Manohar et al reported variation in this iodide impurity in CTAB from lot-to-lot, which hindered nanorod growth. [29] Recent work by Jin et al demonstrated that Br À indeed acts as a crucial shape-directing agent for gold nanorod formation in the seed-mediated process. [30] It has also been found that addition of electrolytes has a great impact in controlling the nanocrystal shapes.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Later Manohar et al reported variation in this iodide impurity in CTAB from lot-to-lot, which hindered nanorod growth. [29] Recent work by Jin et al demonstrated that Br À indeed acts as a crucial shape-directing agent for gold nanorod formation in the seed-mediated process. [30] It has also been found that addition of electrolytes has a great impact in controlling the nanocrystal shapes.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18]37,38,40,44,45,50,53,54,67 Gold nanorod sizes can be tuned by altering the ratios of chemicals involved. 14,[16][17][18]20,22,23,[67][68][69] …”
Section: Synthesis Of Gold Nanoparticlesmentioning
confidence: 99%
“…14,69 Cetyl trimethylammonium bromide (CTAB) is crucial as a shape-directing component in this method, 14,69,144 and gold nanorod particles have therefore been subjected to surface modification with methoxy-(polyethylene glycol)-thiol (mPEG-SH) before administration to cells in biomedical applications. Such PEGylated GNR (PEG-GNR) have been shown to be non-toxic for various cell lines.…”
Section: 612140mentioning
confidence: 99%
See 2 more Smart Citations